The Influence of TAM Factors and Social Influence on Attitude Towards and Its Impact on Repurchase Intention (Survey on Shopee Application Users) - Lestari, Diny Dwi; Astuti, Endang Siti; Sunarti, Sunarti (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This study examines a person's behavior, namely, a person's intention to repurchase a product or service that has been used. This study is called the Repurchase Intention. Repurchase intention is the impact of attitude because of TAM factors and social factors. The continuity of a company is not just about getting customers; companies must be able to grow repurchase intentions in consumers. A quantitative study is used to determine the result of the hypothesis—sampling technique using the probability with the Accidental method. Data was collected using a questionnaire distributed to shopee users in Surabaya. There were 180 questionnaires collected. The data analysis technique uses SmartPLS. Results, variables perceived ease of use, perceived usefulness, and social influence have a direct and significant positive effect on Attitude Toward; the variable attitude toward also has a direct and significant positive impact on intention. So that all hypotheses designed in this study can be accepted. Keywords: Technology Acceptance Model, social influence, repurchase intention